The Hellenistic world : new perspectives - Ogden, Daniel; Le Bohec-Bouhet, Sylvie (New perspectives series., 2002)
The history of the hellenistic world has long been more popular than has widely been realized. This volume seeks to contribute to that popularity. Here are fourteen new perspectives on the period from a distinguished and international group of scholars. Their varied papers are grouped together around five themes: Structure and System; King and Court; Family and Kinship; Landscape and People; Art and Image. The book is conceived as a sister-volume to CPW's sucessful Archaic Greece: New Approaches and New Evidence, edited by Nick Fisher and Hans van Wees (1998).